Orthopaedic patients’ emergency department attendance behavior in relation to weather conditions: temperature, rain, day and time, and regional thursday effect - Bayam, Levent; Öznam, Kadir; Güler, Ayşenur; Uyan, Eren; Erdem, Mehmet (My University, 2025)
Great variation was noticed in emergency department (ED) afflux in relation to daily weather conditions, including difficulties in arranging the correct number of orthopaedic on-calls on the floor. This study aimed to quantify the association between the number of patients referred to the orthopaedic team from the ED and weather conditions, particularly daily temperature and rain. Data were obtained from a large state research hospital’s ED attendance. Weather information for the local area for the year was obtained from the regional meteorological office. Data were evaluated using descriptive statistics, with one-way analysis of variance for the relationship between the day of the week and patient numbers, the Pearson test for correlations between daily ED patient flow and daily temperature and the Spearman correlation test for correlations between daily patient flow and daily rain status. A positive and meaningful correlation existed between daily patient influx and daily temperature, along with a negative correlation between daily patient flow and daily rain. Throughout the year, significantly more patients were referred to the orthopaedic team on Thursdays than on any other day of the week. Patients tended to visit the ED more on warm days and days without rain. These results may help in organising daily, monthly or seasonal on-call orthopaedic team requirements despite the challenges. Incorporating climate forecasts into planning the on-call service might help alleviate the stress on the team.
Keywords: Emergency Service; Hospital; Humans; Orthopedics; Rain; Temperature; Weather